MODEL TEOLOGI KONTEKSTUAL DALAM PENDIDIKAN SENI MAENGKET: INTERNALISASI MODERASI BERAGAMA BERBASIS KEARIFAN LOKAL MINAHASA - Alrik Lapian; Denni H. R Pinontoan; Jekson Berdame (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This article investigates how traditional arts, particularly Maengket dance and the Pangucapan Syukur (Thanksgiving) tradition in Minahasa, serve as strategic vehicles for promoting religious moderation and contextual art education. Drawing on ethnomusicology, sociomusicology, and cultural sustainability theory, the analysis demonstrates that the musical architecture of Maengket possesses significant aesthetic, pedagogical, and spiritual dimensions. Findings indicate that these cultural practices are effective in cultivating organic spaces for interfaith dialogue, strengthening shared values, and enhancing social cohesion within a pluralistic community. Furthermore, the study highlights the critical need to adapt traditional arts into formal educational curricula and to utilize digital platforms for broader outreach to youth. Ultimately, by integrating artistic expression, local wisdom, and technology, this research offers a sustainable model for education and religious moderation that aligns with the evolving social landscape of Indonesia